Interpretation of the pressure-induced Raman frequency shift of the ν1 stretching bands of CH4 and N2 within CH4–CO2, N2–CO2 and CH4–N2 binary mixtures. Issue 14 (30th March 2021) - Le, Van-Hoan; Tarantola, Alexandre; Caumon, Marie-Camille
Abstract : The pressure-induced frequency shift of the CH4 and N2 bands is interpreted by quantitatively attributing to the attractive and repulsive solvation mean-force variation using the Lennard–Jones 6-12 potential and the perturbed hard-sphere fluid model. Abstract : The relationships between the frequency shift of the ν 1 stretching bands of CH4 and N2 with pressure (or density) and composition have been previously provided in the literature as reliable parameters for accurate empirical barometers and densimeters for the direct determination of the pressure or density of gas mixtures. However, the latter results still remain a pure description of the experimental data without any interpretation of the physical mechanisms hidden behind the variation trend of the observed peak position. The present paper is devoted to interpreting the origin of the pressure-induced vibrational frequency shifts of the ν 1 stretching bands of CH4 and N2 within CH4 –CO2, N2 –CO2 and CH4 –N2 binary mixtures at the molecular level. Two different theoretical models ( i.e., the Lennard–Jones 6-12 potential approximation – LJ, and the generalized perturbed hard-sphere fluid – PHF) are used to intuitively and qualitatively assess the variation trend as well as the magnitude of the frequency shift of the CH4 and N2 ν 1 bands for an in-depth understanding. Thereby, the contribution of the attractive and repulsive solvation-mean forces to the variation of the Raman frequency shift as a function of pressure and composition is assessed. A predictive model of the variation trend of the frequency shift of the CH4 ν 1 band as a function of pressure (up to 3000 bars), density and composition within CH4 –N2 and CH4 –CO2 binary mixtures is then provided.